Liquid-Liquid Phase Behavior of Solutions of 1-Octyl- and 1-Decy1-3-methylimidazolium Bis(trifluoromethylsulfonyl)imide (C(8,10)mimNTf(2)) in n-Alkyl Alcohols - Vale, Vlad R.; Rathke, Bernd; Will, Stefan; Schröer, W. (Journal of Chemical and Engineering Data, 2010)
Systematic measurements of liquid-liquid phase diagrams of binary mixtures of the ionic liquids 1-octyl-3-methylimidazolium bis(trifluoromethylsullonyl)imide (C(8)mimNTf(2)) and 1-decy1-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (C(10)mimNTf(2)) with n-alkyl alcohols (1-octanol, 1-nonanol, 1-decanol, 1-undecanol, 1-dodecanol, 1-tetradecanol, 1-hexadecanol, 1-octadecanol, and 1-eicosanol) were performed. The phase diagrams were obtained at atmospheric pressure in the temperature range (283 to 423) K applying the cloud-point method on a set of samples. With the assumption of Ising criticality, analysis of the shapes of the phase diagrams yielded data on the critical points and the parameters characterizing the width and the asymmetry of the coexistence curves.